2016
DOI: 10.1002/aur.1620
|View full text |Cite
|
Sign up to set email alerts
|

Aging and autism spectrum disorder: Evidence from the broad autism phenotype

Abstract: This study investigated for the first time the broad autism phenotype (BAP) in the context of older adulthood and its associations with real-world executive function, social support, and both depression and anxiety symptomatology. Based on self-ratings of autistic traits, 66 older adults (60+ years old, range = 61-88) were split into BAP (n = 20) and control (n = 46) groups. Individuals in the BAP group, even after controlling for age, education level, sex, and health problems, exhibited more real-world execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
31
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 57 publications
11
31
0
2
Order By: Relevance
“…Collectively, results support our hypothesis that the cognitive profile of middle‐age adults with ASD mirrors that observed in younger persons with ASD, namely greater difficulty on an executive function task, which relies on the frontal lobe (WCST), but not on tests subserved by mid and posterior brain regions [AVLT and EFT; Boucher et al, ; Mottron et al, ; Russo et al, ]. Our results are consistent with the small body of literature assessing cognition in older adults with ASD, or with the broader autism phenotype, who also found weaknesses in the executive domain [Geurts & Vissers, ; James et al, ; Lever & Geurts, ; Wallace et al, ]. Another study of older adults used a modified version of the WCST [Geurts & Vissers, ] and found that older adults with ASD performed equivalently to NTs on a less difficult, modified version; whereas the current study found significant differences in numbers of errors performed on the task.…”
Section: Discussionsupporting
confidence: 89%
“…Collectively, results support our hypothesis that the cognitive profile of middle‐age adults with ASD mirrors that observed in younger persons with ASD, namely greater difficulty on an executive function task, which relies on the frontal lobe (WCST), but not on tests subserved by mid and posterior brain regions [AVLT and EFT; Boucher et al, ; Mottron et al, ; Russo et al, ]. Our results are consistent with the small body of literature assessing cognition in older adults with ASD, or with the broader autism phenotype, who also found weaknesses in the executive domain [Geurts & Vissers, ; James et al, ; Lever & Geurts, ; Wallace et al, ]. Another study of older adults used a modified version of the WCST [Geurts & Vissers, ] and found that older adults with ASD performed equivalently to NTs on a less difficult, modified version; whereas the current study found significant differences in numbers of errors performed on the task.…”
Section: Discussionsupporting
confidence: 89%
“…Paralleling these studies, high rates of depression and anxiety have also been identified in individuals with BAP traits (Wainer et al, 2013) and in family members of individuals with ASD (Ingersoll et al, 2011;Wilcox et al, 2003). To date, only one study has examined mood in BAP older adults, and found greater self-reported depression and anxiety in those meeting criteria for the BAP than COA (Wallace, Budgett et al, 2016). Rates of depression among neurotypical older adults are no lower than across the lifespan (Beekman, Copeland, & Prince, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…To our knowledge, only one study has previously examined EF in later life within the BAP (Wallace, Budgett, & Charlton, 2016). Wallace, Budgett et al (2016) examined self-reported BAP traits, EF difficulties, and both depression and anxiety in adults over 60 years old.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who exhibit more BAP traits report experiencing more social and interpersonal problems [ 50 , 52 ]. Additionally, recent evidence suggests that BAP traits in older adults are associated with lower levels of social support, and increased self-reported levels of depression and anxiety [ 53 ]. Given the findings discussed above, it would be of interest to examine the relationship between the ESCoT, measures of intelligence and the BAP, and compare these to the findings of established tests.…”
Section: Introductionmentioning
confidence: 99%